Trans-crocin 4 is not hydrolyzed to crocetin following i.p. administration in mice, while it shows penetration through the blood brain barrier. - Evangelia Karkoula; Lemonakis, Nikolaos; Kokras, Nikolaos; Dalla, Christina; Gikas, Evagelos; Skaltsounis, Alexios-Leandros; Tsarbopoulos, Anthony (Fitoterapia, 2018)
A novel, fit-for-purpose, highly sensitive, analytical UPLC-PDA methodology was developed and fully validated, according to ICH, FDA and EMA guidelines, for the rapid and accurate quantification of trans-crocin 4 (TC4) and crocetin (CRC) in mice plasma and brain after i.p. administration. A PDA based methodology shows a wider applicability as it is cost effective and can be easily and seamlessly adopted by the pharma industry. The separation of the analytes was performed on a C18 Hypersil Gold column with 2.5 min run time, employing the internal standard (ISTD) methodology. The two methods were successfully applied for the determination of CRC and TC4 in mouse plasma and brain after i.p. administration of TC4 (50 mg/kg) in a time range of 0-240 min. Due to the selection of i.p. administration route, the first-pass metabolism and/or gastric hydrolysis were bypassed, a fact that enhanced the bioavailability of TC4. Furthermore, TC4 was found to be capable of crossing the Blood Brain Barrier (BBB) and build up levels in the mouse brain, regardless of its highly hydrophilic character. CRC was not detected in any plasma or brain sample, although it has been reported that TC4 quickly hydrolyzes to CRC after p.o. administration. Therefore i.p. administration could be used in the case of TC4 for the accurate determination of its biological role. Overall, the developed methodology offers important information about the bioavailability of TC4 in mouse plasma and for the first time, demonstrates the ability of TC4 to penetrate the BBB and localize inside the brain.
Keywords: Animals; Biological Availability; Biological Transport; Blood-Brain Barrier; Brain Chemistry; Carotenoids; Chromatography, High Pressure Liquid; Male; Mice